Connecting or constructing academic literacies on Facebook - Bassett, Mark (ASCILITE, 2015)
This paper outlines proposed doctoral research into how postgraduate students develop academic literacies within the bounds of learning theories and Web 2.0 tools that their lecturers select. Lea and Street’s (1998) academic literacies approach, which views literacies as contested social practices, forms the overarching view of literacy in this research. Over one semester, multiple case studies of postgraduate students will be conducted as they complete a paper within their subject of study. Students will use a private Facebook community to complete learning tasks and engage in student initiated discussions. The learning tasks will provide opportunities to examine the student experience of both the constructivist and connectivist paradigms. The aim is to further understanding of the student experience that can inform the creation of sound, theory driven Web 2.0-based learning tasks that effectively assist students in the development of their academic literacies. Feedback on the proposed research is sought from the Ascilite community.
Keywords: Facebook; Academic literacies; Constructivism; Connectivism